2016
DOI: 10.1093/hsw/hlw023
|View full text |Cite
|
Sign up to set email alerts
|

The Subjective Experiences of Attention-Deficit/Hyperactivity Disorder of Chinese Families in Hong Kong: Co-Construction of Meanings in Multiple Family Groups: Table 1:

Abstract: The subjective experiences of Chinese children in Hong Kong with attention-deficit/hyperactivity disorder (ADHD) are underexplored. This article reports the results of a qualitative study that aims to understand the subjective experiences of children with ADHD in Hong Kong, taken from among a clinical sample of Chinese families with children struggling with ADHD who have participated in cross-disciplinary research of multiple family groups (MFG). The participating children revealed the subjective experiences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Because family caregivers with affiliate stigma may not spontaneously seek clinical assistance for their children with ADHD, health care professionals can perform outreach in communities to provide psychoeducation [21]. Caregivers' subjective experiences should be emphasized and carefully examined to identify their needs [53]. Caregivers with high affiliate stigma may also benefit from interacting with those with low affiliate stigma; in the interaction process, they may develop mutual understanding and support that help reduce affiliate stigma [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because family caregivers with affiliate stigma may not spontaneously seek clinical assistance for their children with ADHD, health care professionals can perform outreach in communities to provide psychoeducation [21]. Caregivers' subjective experiences should be emphasized and carefully examined to identify their needs [53]. Caregivers with high affiliate stigma may also benefit from interacting with those with low affiliate stigma; in the interaction process, they may develop mutual understanding and support that help reduce affiliate stigma [53].…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers' subjective experiences should be emphasized and carefully examined to identify their needs [53]. Caregivers with high affiliate stigma may also benefit from interacting with those with low affiliate stigma; in the interaction process, they may develop mutual understanding and support that help reduce affiliate stigma [53]. Moreover, behavioral parent training to reduce affiliate stigma should be provided to family caregivers of children with ADHD with adequate adjustments for caregivers' and children's sociodemographic characteristics and ADHD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Singh’s () qualitative study of 150 children from the US and the UK has shown that medication has helped children with ADHD to enhance their capacity to meet the normative standards of the society they live in, even though they experienced intolerable self‐alienation while on medication. Similar themes were discerned in a qualitative study done on twenty families in Hong Kong involving a ‘press conference’, an MFT activity that creates a playful context in which the children are to act as ‘experts’ and the parents as ‘reporters’ in order to encourage cross‐generational dialogue between the children with ADHD ( n = 21) and their parents regarding the meaning of ADHD and medication (Wan et al, ). Some of the children perceived taking medication to be the best means of assisting their helpless mother to cope with pressure from school.…”
Section: Literature Reviewmentioning
confidence: 65%
“…Despite the fact that these children have been struggling with self‐control, they have a capacity for self‐agency (Singh, ). Nevertheless, having been limited by their scope (Singh, ; Wan et al, ), these studies had not explored the children’s subjective experiences with an MFT. Such information is crucial.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Especially, it needs further study why the caregivers rated CAIS as effective but visited the psychiatric clinics for further evaluation and treatment. Caregivers' subjective experiences should be emphasized and carefully examined to identify their needs [40]. Health care professionals should perform an in-depth investigation of family caregivers' motivation for employing CAIS for their child's ADHD rather than simply attributing it to caregivers' ignorance or denial of illness.…”
Section: Discussionmentioning
confidence: 99%